Design of Jigs and Fixtures for Hydraulic Press Machine - Taufik R.S; Hirmanto S; Hambali A; Tajul AA (Faculty of Engineering, Universitas Malikussaleh, 2012)
This paper presents the design of jigs and fixtures for hydraulic press machine in manufacturing industries. The current problem in industry is facing the utilization of hydraulic press machine when the demand has increased which occurs on the gripping or holding the workpiece securely. The main objective of this study is to propose a new design of jigs and fixtures for hydraulic press to carry out the gripping problem from existing design. Several design concepts were generated and simulated to analyze using ANSYS software. The design parameters such as maximum deformation, maximum shear stress, number of contact faces, and maximum holding force were presented. Based on the simulation result, the improvement of new jigs and fixtures design for hydraulic press machine was achieved.